Clinicopathological Analysis of Five Cases of NUT Midline Carcinoma, including One with the Gingiva. (14th February 2020) - Zhou, Luting; Yong, Xiang; Zhou, Jun; Xu, Jiankun; Wang, Chaofu
Abstract : Aims . NUT midline carcinoma (NMC) is a rare, poorly differentiated carcinoma defined by the presence of NUT gene rearrangement. In order to better understand the diagnostic and clinicopathologic features of this disease as they pertain to clinical practice, we have herein compiled findings pertaining to 5 cases of NMC at our institution. Methods . Clinicopathological findings from 5 NMC cases were retrospectively reviewed, with histologic findings being reassessed and summarized accordingly. Tumor samples in the present study had been stained for markers including NUT, P63, P40, TTF-1, keratin, CK7, Syn, CD56, CgA, CD34, CD117, EGFR, and Ki-67. All cases were subjected to both fluorescence in situ hybridization (FISH) and followed up. Results . Of these 5 NMC cases, 2 were males and 3 were females, with ages ranging from 26 to 69 years. A total of 2 cases localized to the lung, 1 to the larynx, 1 to the maxillary gingiva, and 1 to the orbital cavity. Upon microscopic assessment, these tumors appeared as clusters of small rounded cells with interstitial neutrophil infiltration. Squamous epithelial differentiation varied between samples. NUT staining revealed strong diffuse nuclear staining in tumor cells, and FISH confirmed the presence of NUT gene translocation in these samples. Conclusions . NMC is a form of highly invasive cancer that can manifest in a number of tissues including the gingiva. NMC tumors have a fairly well-defined pathological morphology, and both immunohistochemistry and FISH are valuable for NMC diagnosis.